Computational Study of Excitation Coil for Magnetic Particle Imaging Application Using JMAG Software - Mohd Fauzi, Muhammad Fakhrul Syazwan; Othman, Nurmiza (Evolution in Electrical and Electronic Engineering, 2022)
Magnetic particle imaging (MPI) is a novel tomographic approach for three-dimensional (3D) imaging that employs magnetic nanoparticles (MNP) as a tracer. MPI is made up of three major components: MNP, magnetic coils, and an image reconstruction approach. The scanning process is made more difficult and constrained by the complicated topology of the skin surface, the physical qualities, configuration, and the dimension of the coil, and the high input current for excitation. By increasing the magnetic field induction, image quality may be increased. This project focused on the computational study of excitation coil for MPI application by using JMAG software. Through this study, the parameter and specifications of the excitation coil were developed and simulated using JMAG software. Two types of design are being simulated in this project, Design A and Design B. These two designs have a similar shape but Design B is divided into small sub-coils. Both designs are simulated with the ferrite and without ferrite at the core of the excitation coil to see the difference in the magnetic field produced by the excitation coil. From the simulation, the maximum value of contour produced by the excitation coil was investigated to study the distribution of magnetic field induction around the coil. As a result, the difference value with ferrite and without ferrite produced by design A is 106.73µT and the difference value with ferrite and without ferrite produced by design B is 105.21 µT. For this project used two types of material for the excitation coil core which is used ferrite and without ferrite can be summarized and can be developed the excitation coil core using ferrite. This project has proven that ferrite used as excitation coil core produced a stronger maximum value of magnetic flux density than excitation coil core that did not use ferrite for both designs A and B. Finally, a portable single-sided MPI scanner with a simple coil arrangement, compact size, and low current can be constructed for MPI applications to generate a high magnetic field induction in the future.